The Efficacy of Using a Sterile Glove Technique for Retrieval of the Gall Bladder Through the Epigastric Port in Preventing Post-Operative Infections During Laparoscopic Cholecystectomy - Munir Ahmad, Hidayat Ullah, Amir Hamza, Asif Din, Aamir Khan, Syed Majid Ali Shah, (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To compare the efficacy of using sterile surgical gloves to retrieve the gall bladder through the epigastric port in laparoscopic cholecystectomy as compared to the direct retrieval technique in terms of surgical port site infections. Study Design: Randomized Controlled Trial Setting: Department of Surgery, Khyber Teaching Hospital, Peshawar. Duration: From 1st August, 2022, to 31st January, 2023. Methodology: After attaining approval from the Hospital ethical committee all patients meeting the inclusion criteria were included in the study. The patients were allocated in two groups through blocked randomization: Group A (use of sterile glove for extraction) and Group B (direct removal of gall bladder). Results were analyzed on Statistical Package for Social Sciences (SPSS) Version 23 and depicted in the form of description and statistical tables. Results: The mean age was 39.64 years ± 3.22 in group A and 38.25 years ±13.3 in group B and most patients were females in both groups, group A (n=40, 80%) and group B (n= 69, 86.3%).In group, A ,11 patients were diabetic (22%) and 5(10%) of the patients developedPSI at the epigastric port, 3(27.3%) in diabetics and 2(5.1%) in non-diabetics, p-value 0.031. In group B, 19 patients were diabetic (23.8%) and10 (12.5%) patients developed PSI, seen on 7th day follow up, 8 in diabetics (80%) and 2 non-diabetics(20%), p-value <0.01. The correlation between diabetes mellites and PSIs showed significant correlation p-value <0. 001.However,no significant correlation was seen between both groups in terms of PSIs, p-value 0.530. Conclusion: Even though it was observed that using retrieval bags relatively decreases the incidence of port site infections in laparoscopic cholecystectomy, the percentage is not notable enough to justify for its impact on operative time. Keywords: Laparoscopic Cholecystectomy, Epigastric Port,Glove Technique, Direct Removal, Port Site Infections